Banks of a feather: The informational advantage of being alike - Peter Bednarek; Valeriya Dinger; Alison Schultz; Natalja von Westernhagen (Deutsche Bundesbank, 2023)
Banks lend more to banks that are similar to them. Using data from the German credit register and proprietary supervisory data on the quality of banks' loan portfolio, we show that a similar portfolio of the lending and borrowing bank helps to overcome information asymmetries in interbank markets. While interbank lenders generally do not adjust their lending to information on the counterparty's portfolio quality, banks with an exposure to similar industries and regions strongly react to this private information. Lending between similar banks is particularly important for borrowers with an opaque loan portfolio, which do not obtain credit from dissimilar peers.
Keywords: E50; G11; G20; G21; 330; Peer monitoring; interbank markets; asymmetric information; portfolio quality; portfolio similarity; systemic risk and contagion